Socio-Political Criticism in Buya Hamka's Tafsir Al-Azhar: A Thematic Study of the Value of Justice - Trisno Susilo; Andri Nirwana, AN; Hakimuddin Salim; Kuswardani Dyah Ayu Kusumaningrum (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study examines the dimension of socio-political criticism in Tafsir Al-Azhar by Buya Hamka with a focus on the value of justice as the central theme. The Tafsir of Al-Azhar is not only a monumental work in the Islamic scientific treasures in the archipelago, but also a reflection of the thinking of a scholar who is responsive to the socio-political dynamics of his time. Hamka, as a mufasir as well as a social activist, integrates the textual understanding of the Qur'an with the historical context and empirical reality of society, resulting in contextual and applicative interpretations. This study uses a qualitative method with a hermeneutical-critical approach to analyze how Hamka constructs the concept of socio-political justice through his interpretation of the verses of the Qur'an. The findings of the study show that Hamka's socio-political criticism in Tafsir Al-Azhar includes three main dimensions: first, criticism of the arbitrariness of rulers and abuse of power; second, advocacy for the rights of the oppressed and marginalized groups; and third, emphasis on the principles of deliberation and political participation as a mechanism for the realization of justice. Hamka emphasized that justice is a fundamental value in Islam that must be implemented concretely in the political system and social structure. The concept of justice in Tafsir Al-Azhar is not limited to the individual-spiritual dimension, but extends to the collective-structural level that includes economic distribution, legal equality, and political participation. This research makes a theoretical contribution to the study of Indonesian contextual interpretation and a practical contribution to the development of Islamic political ethics based on the Qur'an.